Editorial - Bogaert, Koen (Afrika Focus, 2013)
To conclude, I want to refer briefly to the content of our next issue. Ray Bush’s article for example can be read with Žižek’s notion of objective violence hovering in the background. We also have three other interesting articles on a diverse range of topics: urbanization and its comparative elements, music as a point of social connection in the post-colonial city of Lisbon, and the Equality Guarantee under the Ethiopian Constitution. Also, we publish three reports based on recently completed doctoral research. Finally, AF is now also active on some of the main social media networks, Facebook, Twitter, and Academia.Edu, an academic social media networ